The Epistemology of Islamic Inheritance Disputes - Bari, Abdul (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This research explores the epistemology of Islamic inheritance law in Indonesia, rooted in the Quran, Hadith, and ulama's ijtihad, yet influenced by customary and national law. Using normative legal research with literature study, it finds that inheritance disputes arise from plural legal systems and interpretive differences. An integrative approach based on maqasid al-shariah is proposed to ensure justice and civilized resolution.